Neutron diffraction and neutron imaging residual strain measurements on offshore wind monopole weldments - Jacob, Anaïs; Mehmanparast, Ali; Kelleher, Joe; Burca, Genoveva (Elsevier, 2018)
Residual stress measurement is of fundamental interest in order to estimate the service life of engineering components and structures subjected to various loading conditions operating in different environments. Destructive and non-destructive techniques are used for the evaluation of residual stresses. Neutron diffraction, as a non-destructive technique, is widely used to measure the elastic strain component of a specific atomic plane from which residual stresses can be calculated. Neutron imaging is an alternative technique which enables residual stresses to be measured through strain mapping of the area of interest. In this study, neutron diffraction measurements were performed in conjunction with neutron imaging to evaluate residual strains in a compact tension, C(T), specimen extracted from a welded plate made of S355 structural steel. Neutron diffraction and imaging are two complementary techniques which have been employed in this work by performing measurements on the Engin-X and newly developed IMAT instruments, respectively, at the Rutherford Appleton Laboratory. Neutron diffraction residual strain measurements in all three directions were conducted within the Heat Affected Zone (HAZ) of the weld area whereas longitudinal residual strains were measured using the neutron imaging technique. A comparison of the neutron diffraction and neutron imaging preliminary results has shown that neutron imaging can provide acceptable measure of residual strains compared to those of obtained from neutron diffraction. The results have been discussed in terms of the possible sources of error encountered in each measurement technique and the accuracy of each technique against the other.
Keywords: Residual stresses; welded joints; neutron diffraction; neutron imaging